(untitled) (The Research of Medical Science Review, 2025)
Introduction: Erectile Dysfunction is one of the most significant issues facing the male population across the globe. Several issues are associated with ED in which the most common are psychological issues. It has been found that men who suffer from anxiety problems have a significantly increased likelihood of getting erectile dysfunction (ED). Objectives: This study aimed to access the prevalence of anxiety among patients with ED and its association with ED. Methodology: A cross-sectional study was carried out in the urology department of a private hospital of Peshawar. Data was collected from 385 participants using two standard questionnaires. Consents were granted from all the participants. Results: The majority (58%) of the participants were reported moderate level of anxiety while more than half (51%) of the participants were reported mild to moderate ED. There was significant association (P=0.01) among level of anxiety and ED. Mild to moderate and severe anxiety is significantly associated with moderate and severe ED. Conclusion: Erectile dysfunction is mostly prevalent among the men and it is associated with psychological consequences such as anxiety. The findings of this study have proved that erectile dysfunction is significantly associated with anxiety.